Efficacy of liposomal antibiotic therapy in a rat infusion model of Escherichia coli peritonitis - Martineau, L; Shek, P N (Critical care medicine, 1999)
To compare the potential therapeutic effect of liposomal vs. free cefoxitin. Randomized, controlled study, using a rat model of peritonitis. Government research facility. Male Sprague-Dawley rats. Rats were infused intraperitoneally with 6.5 x 10(8) colony forming units of Escherichia coli over 12 hrs. Animals were then randomized to receive intravenous saline, free cefoxitin, liposomal cefoxitin, or plain liposomes twice daily until they were killed. Free cefoxitin significantly reduced the number of E. coli after 24 hrs compared with saline treatment in both liver and spleen. However, liposomal cefoxitin further decreased the bacterial content by five-fold to ten-fold in these organs. Minimal bactericidal effect was observed in animals injected with plain liposomes. Although administration of liposomal cefoxitin for 7 days further reduced bacterial counts in liver and spleen, there was no apparent beneficial bactericidal effect of free cefoxitin over saline at 7 days. There was approximately a ten-fold reduction in bacterial content in the lungs after 24 hrs in all three treatments, but no further reduction was observed after 7 days. There was no difference in 7-day survival rate in animals treated with plain liposomes or saline (45% vs. 39%). Although survival tended to increase with free cefoxitin treatment (64%), this outcome was significantly improved with the use of liposomal cefoxitin (82%). Liposomal cefoxitin enhanced bacterial killing in liver and spleen in this model of E. coli peritonitis. It also improved survival outcome relative to no treatment but not compared with free cefoxitin.